PERANCANGAN SISTEM INFORMASI BERBASIS E-COMMERCE UNTUK PENINGKATAN PENJUALAN PRODUK JERSEY OLAH RAGA - Henri Abdiel Simbolon; Victor Marudut Mulia Siregar (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2018)
This study aims to create a web-based sales system in Pematangsiantar Stars Jersey distribution store. The design and manufacture is intended to facilitate the management of sales and purchase data, as well as facilitate shop employees. So that store employees can easily enter sales and purchase data without having to write it in a notebook or sales book. Makes it easier for shop owners to check sales data quickly and efficiently. This research is expected to be able to create a more effective means of buying and selling than the previous method in the Pematangsiantar Stars Jersey Store, thereby making it easier to record sales and purchases at the Stars Jersey Shop. Keywords: Sales, Effective, Design, Web, Data